Data augmentation analysis of vehicle detection in aerial images - Nguyen, Khang (Journal of Computer Science and Cybernetics, 2023)
Drones are increasingly used in various application domains including surveillance, agriculture, delivery, search and rescue missions. Object detection in aerial images (captured by drones) gradually gains more interest in computer vision community. However, research activities are still very few in this area due to numerous challenges such as top-view angle, small-scale object, diverse directions, and data imbalance. In this paper, we investigate different data augmentation techniques. Furthermore, we propose combining data augmentation methods to further enhance the performance of the state-of-the-art object detection methods. Extensive experiments on two datasets, namely, AERIAU, and XDUAV, demonstrate that the combination of random cropped and vertical flipped data boosts the performance of object detectors on aerial images.